2016
DOI: 10.1049/mnl.2016.0199
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of WO 3 crystalline nanoplate on FTO glass and their application in electrochromism

Abstract: Tungsten trioxide (WO 3) thin films are of great interest as counter electrodes in electrochromic (EC) devices such as 'smart window' for energy-efficient buildings. Uniform WO 3 nanoplates filmed as EC working electrodes were fabricated on seed-free fluorine-tin-oxide (FTO) coated glass via a facile and addictive agent-free hydrothermal process. The WO 3 nanoplates were characterised by scanning electron microscopy and the X-ray photoelectron spectroscopy. The morphological analysis of the film showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Bismuth nitrate pentahydrate Bi(NO 3 ) 3 ·5H 2 O, titanium butoxide (TBOT), ethylene glycol [(CH 2 OH) 2 ], and potassium iodide (KI) were purchased from Sinopharm Chemical Reagent Co., Ltd. Fluorine‐doped tin oxide (FTO) conducting glasses were purchased from Aladdin Industrial Corporation . Concentrated hydrochloric acid (HCl), ethanol, acetone, and methanol were purchased from Aladdin Industrial Corporation …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth nitrate pentahydrate Bi(NO 3 ) 3 ·5H 2 O, titanium butoxide (TBOT), ethylene glycol [(CH 2 OH) 2 ], and potassium iodide (KI) were purchased from Sinopharm Chemical Reagent Co., Ltd. Fluorine‐doped tin oxide (FTO) conducting glasses were purchased from Aladdin Industrial Corporation . Concentrated hydrochloric acid (HCl), ethanol, acetone, and methanol were purchased from Aladdin Industrial Corporation …”
Section: Methodsmentioning
confidence: 99%
“…7,8 Concentrated hydrochloric acid (HCl), ethanol, acetone, and methanol were purchased from Aladdin Industrial Corporation. 9,10 Before the hydrothermal synthesis of TiO 2 nanorods, acetone, ethanol, and deionized water were used to ultrasonically clean the FTO substrate. A TNR film can be prepared on an FTO substrate by a simple hydrothermal method.…”
Section: Preparation Of Tnrmentioning
confidence: 99%
“…In this paper, we report the synthesis of WO3 nanoplates prepared by a simple hydrothermal synthesis method.. Several studies have reported the production of tungsten oxide using hydrothermal techniques but tungsten oxide structures have been obtained as a powder by long-term synthesis at high temperatures by a salt-acid assisted process [1,9,[11][12][13][14]. It has also been formed without the use of any seed layers on the substrate [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, growing nanotree-like WO 3 structures from nanowires aligned vertically on the substrate would more efficiently use the substrate surface, thus increasing the WO 3 active surface area and improving the EC performance. 23−26 Solvothermal processing is a facile method for the synthesis of uniquely structured, high surface area, crystalline WO 3 materials, including nanorods, 27−29 nanowires, 30−32 nanosheets, 33,34 nanohoneycombs, 35 nanothorns, 36 and nanoflowers. 37 Most reported synthesis approaches to form WO 3 nanostructures require a seed layer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Solvothermal processing is a facile method for the synthesis of uniquely structured, high surface area, crystalline WO 3 materials, including nanorods, nanowires, nanosheets, , nanohoneycombs, nanothorns, and nanoflowers . Most reported synthesis approaches to form WO 3 nanostructures require a seed layer.…”
Section: Introductionmentioning
confidence: 99%